A bi-objective model to include workers' vibration exposure in assembly line design. Issue 13 (3rd July 2021) - Finco, Serena; Abdous, Mohammed-Amine; Calzavara, Martina; Battini, Daria; Delorme, Xavier
Abstract : In several occupational sectors, workers are daily exposed to vibrations induced by automatic, pneumatic, or electric tools, with a consequent increase of musculoskeletal disorders. In this paper, a bi-objective manual assembly line design model is proposed, aiming to avoid excessive daily vibration exposures. The developed model allows to minimise both total equipment costs and vibration levels by respecting the threshold values defined in the ISO 5349-1. The ϵ -constraint approach is used to address both objectives and to find the Pareto frontier. The model is applied to several instances to evaluate the computational limit of the solving method, as well as to an industrial case to provide managerial guidelines. The results show that the method can solve small and medium size instances. Moreover, the case study points out that safe vibration exposure levels can be achieved also with a low additional investment and that solutions equal from an economic point of view can be different from a vibrations exposure one.